Impact of Antibiotic Prescribing Patterns on Susceptibilities of Uropathogens in Children below 24 Months Old - Ji Young Park; Hyun Mi Kang; Eun Min Kwak; Jung-Woo Rhim; Yo Han Ahn; Hyunju Lee; Dae Chul Jeong; Jin Han Kang (Antibiotics, 2020)
Monitoring regional antibiotic resistance patterns of uropathogens are important for deciding suitable empirical antibiotics for urinary tract infections (UTIs) in children. This study aimed to investigate regional differences in antimicrobial susceptibility patterns of E. coli and Klebsiella spp. in children below 24 months old, diagnosed with their first episode of UTI, and to find factors associated with an increased risk for UTI caused by extended-spectrum β-lactamase (ESBL)-producing uropathogens. This was a retrospective cohort study of children diagnosed between 2011 and 2017 in four different hospitals located in four different regions of South Korea; regions A, B, C, and D. The government’s big data repository was used to acquire data on regional antibiotic prescriptions. The pooled antimicrobial susceptibilities of E. coli and Klebsiella spp. (n = 2044) were as follows: ampicillin–sulbactam (61.0%), 3rd generation cephalosporin (3C) (82.8%), and trimethoprim–sulfamethoxazole (72.0%). Multivariate analysis showed that children diagnosed at hospital A (OR, 1.8; 95% confidence interval [CI], 1.2–2.6; P = 0.002) and every year that increased in the study period (OR, 1.1; 95% CI, 1.1–1.2; P < 0.001) were factors associated with an increased risk for UTIs with ESBL-producers. Regions A and B had significantly higher amounts of oral 3Cs prescribed compared to regions C and D (P = 0.009), which correlate with hospitals in the regions that had higher proportions of UTIs with ESBL-producing uropathogens (A and B vs. C and D, P < 0.001). Therefore, children in certain regions are at a higher risk for UTIs caused by ESBL-producers compared to other regions, which correlate with regions that had higher amounts of oral 3Cs prescribed.